Study of the effect of polytetrafluoroethylene shedding from channel surface on droplet flow characteristics using lattice Boltzmann method. (March 2023) - Liao, Jiadong; Yang, Guogang; Li, Shian; Shen, Qiuwan; Jiang, Ziheng; Wang, Hao; Zhang, Guoling
Abstract: A pseudopotential multi-relaxation time (MRT) lattice Boltzmann method (LBM) is used to simulate the flow of the droplet in the cathode flow channel of a proton exchange membrane fuel cell (PEMFC) with polytetrafluoroethylene (PTFE) random shedding. The model can achieve a large density ratio and viscosity ratio, independent adjustment of surface tension, and satisfy thermodynamic consistency. Considering the effects of different droplet radii, contact angles, airflow velocities, and PTFE random shedding ratios, it is found that the larger the droplet radius, contact angle, and airflow velocity, the larger the droplet movement velocity and the faster the discharge of the channel, but the larger the pressure difference between the inlet and outlet of the channel will be caused in the case of 10% PTFE shedding. The droplet shape change is greatly influenced by the droplet radius and contact angle, and the airflow velocity has no significant effect on it. The larger the PTFE random shedding ratio, the greater the effect on the droplet motion velocity, the longer the droplet discharge time from the channel, the smaller the pressure difference between the inlet and outlet of the channel, and the more drastic the shape change during the droplet movement. Graphical Abstract: ga1